Correlation analysis of geomagnetic parameters based on seasonal changes / Nur Suhaili Abdul Samad - Abdul Samad, Nur Suhaili (2016)
Geomagnetic parameters at different seasons and different latitudes have different variations. The focus on this paper is mainly to analyze the correclation of geomagnetic parameters which are horizontal (H), declination (D) and vertical (Z) based on seasonal changes.